إمكانية استخدام النظم الخبيرة في تطوير مهنة مراقبة الحسابات : دراسة لآراء عينة من مراقبي الحسابات في العراق - د. زياد هاشم السقا; د. ناظم حسن رشيد (PROSPECTIVE RESEARCHES, 2023)
In the light of expert systems applications in various fields. It is for the auditors to understand the importance of the use of those applications in the development of different areas under scrutiny. As the transfer of knowledge and experience of expert, scarce, human auditors to new auditors, conserve and facilitate their use in a particular area is one of the key aspects in development of the profession of auditing. It can be said that the revolution of modern technology has provided a great opportunity for accountants and auditors to take advantage of the advantages and potential of IT experience in the field of electronic systems, and to take advantage of these systems in the field of auditing. The auditors must be able to adapt and adjust quickly with this technology.